No Matter How Long the Night, the Day is Sure to Come: Differences, Diversity and Identities in Caribbean-British Poetry since 1945 (American & British Studies Annual, 2012)
English poets of ethnic origin have traditionally responded to their social condition with greater immediacy than the politicians of their time. This article focuses on the process of exclusion and inclusion of English poets with an ethnic background into the canon of English literature. It demonstrates the ways poets search and fight for their ethnic and/or English identity. Special attention is paid to Claude McKay, Louise Bennett, James Berry, John Agard, Linton Kwesi Johnson, Benjamin Zephaniah, Levi Tafari, Grace Nichols, and Jean Binta Breeze, whose works are examined in order to explore the notion of "otherness." The concepts discussed also include social prejudice, conflicting identities, social hierarchy, multicultural diversity of Englishness, and mainstream attitudes and images in contrast with ethnic imagery. The poetry of these poets is analysed in relation to the Empire Windrush generation of Caribbean-British poets, the post-war immigration policy of the UK, and in the context of diasporic literature.
Keywords: ethnic poetry; Empire Windrush; British literature; British-Caribbean; postcolonial; multicultural; Claude McKay; Louise Bennett; James Berry; John Agard; Linton Kwesi Johnson; Benjamin Zephaniah; Levi Tafari; Grace Nichols; Jean Binta Breeze